2013
DOI: 10.1103/physreva.88.023626
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional theory for the spin-1 bosons in a one-dimensional harmonic trap

Abstract: We propose the density-functional theory for one-dimensional harmonically trapped spin-1 bosons in the ground state with repulsive density-density interaction and anti-ferromagnetic spin-exchange interaction. The density distributions of spin singlet paired bosons and polarized bosons with different total polarization for various interaction parameters are obtained by solving the Kohn-Sham equations which are derived based on the local density approximation and the Bethe ansatz exact results for homogeneous sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…There has been significant interest in using BALDA to understand the derivative discontinuity in both DFT and TD-DFT [123,245,248,252]. Additionally, the BALDA approach has been developed for other BA-solvable fermionic lattice systems aside from the Hubbard model [3,156,198,246], such as the Anderson model [24,122,139], as well as bosonic systems [85,238,239].…”
Section: Baldamentioning
confidence: 99%
“…There has been significant interest in using BALDA to understand the derivative discontinuity in both DFT and TD-DFT [123,245,248,252]. Additionally, the BALDA approach has been developed for other BA-solvable fermionic lattice systems aside from the Hubbard model [3,156,198,246], such as the Anderson model [24,122,139], as well as bosonic systems [85,238,239].…”
Section: Baldamentioning
confidence: 99%
“…These states, either degenerate for U 2 = 0 and U 0 → ∞ or quasi-degenerate for the other cases, correspond to different density profiles of the three components with spin m = +1, 0, −1 (see [164]). A detailed density functional study with up to N = 30 atoms concluded that the competition between the repulsive density-density interactions, U 0 , and the spin-exchange interactions, U 2 , led to compli-cated density distributions of the three spin components, even when both are kept equal [198]. Note that, in that case, U 2 had the same sign as U 0 , corresponding to the antiferromagnetic case.…”
Section: Spinor Bose Mixturesmentioning
confidence: 99%
“…Immediately after the realization of optical lattice [5], confining spinor bosons in optical lattices becomes one of the hottest research topics in the field of cold atoms and has been extensively investigated [6][7][8][9][10], although the experimental realization of the optical lattice spinor Bose system has been achieved only very recently [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was proposed theoretically [1,2] and realized exper imentally [3], spinor Bose-Einstein condensate has opened a new avenue to investigate magnetic systems by utilizing ultra cold atomic gases [4]. Immediately after the realization of optical lattice [5], confining spinor bosons in optical lattices becomes one of the hottest research topics in the field of cold atoms and has been extensively investigated [6][7][8][9][10], although the experimental realization of the optical lattice spinor Bose system has been achieved only very recently [11].…”
Section: Introductionmentioning
confidence: 99%